Rare Earth-Promoted Nickel Oxide Nanoparticles as Catalysts for N2O Direct Decomposition - Abu-Zied, Bahaa M.; Bawaked, S. M.; Kosa, S. A.; Schwieger, Wilhelm (Catalysts, 2016)
For this paper, a series of rare earth (Gd, La, Sm) promoted NiO catalysts were prepared by using the microwave-assisted precipitation method and tested for N2O direct decomposition. The obtained solids have been characterized by using various techniques. X-ray diffraction (XRD) results revealed that the incorporation of RE oxides into NiO significantly decreases its crystallite size. Field-emission scanning electron microscopy (SEM) and transmission electron microscopy (TEM) observations indicated that the addition of RE oxides swells the NiO particles yielding particles into a rice-like morphology. N-2 adsorption studies showed a sharp surface area increase as well as mesoporosity development accompanied the RE incorporation. It was found that the RE oxides significantly enhance the NiO activity.
Keywords: greenhouse gas; nitrous oxide; N2O decomposition; promoted-NiO; rare earth oxides